1997
DOI: 10.1016/s0005-2736(96)00230-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of luminal pH on transport of neutral and charged dipeptides by rat small intestine, in vitro

Abstract: Four hydrolysis-resistant dipeptides (D-phenylalanyl-L-alanine, D-phenylalanyl-L-glutamine, D-phenylalanyl-L-glutamate and D-phenylalanyl-L-lysine) were synthesized to investigate the effects of net charge on transmural dipeptide transport by isolated jejunal loops of rat small intestine. At a luminal pH of 7.4 and a concentration of 1 mM the two dipeptides with a net charge of -1 and +1 were transported at substantially slower rates (18 +/- 1.3 and 8.4 +/- 1.3 nmol min(-1)(g dry wt.)(-1), respectively) than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The transport of VACV and GVACV was found to be pH-dependent (Fig. 8), which is consistent with the report on the interaction of positively charged dipeptides with PEPT1 (Temple et al, 1996;Amasheh et al, 1997;Lister et al, 1997). VACV and GVACV have three pK a values (1.90, 7.47, and 9.43) and exist as a mixture of cationic and neutral species at pH 7.4, which is the pH of maximal transport among the range studied.…”
Section: Discussionsupporting
confidence: 90%
“…The transport of VACV and GVACV was found to be pH-dependent (Fig. 8), which is consistent with the report on the interaction of positively charged dipeptides with PEPT1 (Temple et al, 1996;Amasheh et al, 1997;Lister et al, 1997). VACV and GVACV have three pK a values (1.90, 7.47, and 9.43) and exist as a mixture of cationic and neutral species at pH 7.4, which is the pH of maximal transport among the range studied.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, it was found that a decrease in external pH induces an increase in the rate of transport of negatively charged dipeptide, and to a lesser extent of neutral substrates, while an increasing pH is concomitant with transport of positively charged dipeptides. In vitro observations byLister et al (1997) confirmed these results. They investigated the effect of net charge on the transmembrane transport of hydrolysis-resistant dipeptides (Phe-Ala, Phe-Gln and Phe-Glu) in isolated jejunal loops of rat small intestine and the influence of luminal pH.…”
Section: Structure-functionsupporting
confidence: 67%
“…They investigated the effect of net charge on the transmembrane transport of hydrolysis-resistant dipeptides (Phe-Ala, Phe-Gln and Phe-Glu) in isolated jejunal loops of rat small intestine and the influence of luminal pH. Indeed, transport of neutral and negatively charged dipeptides was stimulated by lowering the luminal pH to 6.8, whereas the contrary was described for positively charged dipeptides (Lister et al, 1997). Tripeptide-like β-lactam antibiotics such as anionic cefixime and zwitterionic cefadroxil were also tested for transport by rabbit PepT1, associated with an additional technique of intracellular pH recording by fluorometric measurements.…”
Section: Structure-functionmentioning
confidence: 99%
“…Rat intestinal loops in vitro and vascularly perfused small intestine in situ were used to measure transepithelial fluxes in the intact small intestine as described previously (3,7). Luminal pH was changed using a previously published protocol (8). Isolated murine enterocytes were prepared by enzymatic digestion using haluronidase, and intracellular pH was determined fluorimetrically using carboxy-SNARF (9).…”
Section: Methodsmentioning
confidence: 99%